Numerical study of wind-tunnel sidewall effects on circulation control airfoil flows - Nishino, T; Shariff, K (2010)
Two-and three-dimensional numerical simulations are performed of the flow around a circulation control airfoil (using a Coanda jet blowing overarounded trailing edge) placed in a rectangular wind-tunnel test section. The airfoil model spans the entire tunnel and the span-to-chord ratio of the model is 3.26. The objective of this numerical study, in which we solve the compressible Reynolds-averaged Navier-Stokes equations in a time-resolved manner (but the solutions eventually converge to steady states), is to investigate the physical mechanisms of wind-tunnel side wall effects on the flow, especially in the midspan region. The three-dimensional simulations predict that the Coanda jet flow is quasi-two-dimensional until the flow separates from the trailing edge of the airfoil; however, the spanwise ends of this Coanda jet sheet then three-dimensionally roll up on the side walls of the wind tunnel to form two large streamwise vortices downstream. Careful comparisons between the two-and three-dimensional simulations reveal that the wind-tunnel stream goes below the airfoil more in the three-dimensional cases than in the two-dimensional cases due to the presence of these two streamwise vortices downstream. This results in smaller lift and larger drag being produced at the midspan of the airfoil in the three-dimensional cases than in the two-dimensional cases. © 2010.